Study of Acceptance and Application of Calgary Cambridge Communication Guideline for Doctor-Patient Communication in Primary Health Care - Widyastuti Widyastuti; Mora Claramita; Retna Siwi Padmawati (Review of Primary Care Practice and Education (Kajian Praktik dan Pendidikan Layanan Primer), 2018)
ABSTRACTBackground: Communication is a basic skill that must be acquired by every doctor just like all other clinical skills. One of communication guidelines for doctor-patient that is the most widely used in many countries is the Calgary-Cambridge Communication Guideline (CCCG). However, since CCCG is based on the Western style of communications, a further study is necessary to determine whether CCCG is acceptable and applicable in Indonesia.Methods:  This research was an analytic descriptive study with a cross-sectional design. The research was conducted from December 2016 until January 2017 in Yogyakarta with 58 primary care doctors. The data was collected using the CCCG-based questionnaire method with a cross-cultural adaptation.Results: The CCCG is well accepted although its application is not optimum. The acceptance rate was 4.03 (indicating highly acceptable), while the application rate was 3.74 (indicating occasionally implemented). There was a significant difference between the acceptance and application rates (p<0.01). There were no significant differences between the acceptance rates of Puskesmas (Community and Primary Health Care Center) and non-Puskesmas (p = 0.115) facilities while the application was significantly different (p = 0.001). The application levels of the Puskesmas were lower than those in non-Puskesmas. Additionally, there was no difference in the acceptance or application of CCCG for doctors who have and who have not attended communication training.Conclusion: There was no difference in the acceptance of CCCG, but there was a difference in its application. The application rate at Puskesmas was lower than non-Puskesmas facilities. The experience in communication training did not affect the acceptance and the application rates of CCCG.